PENGARUH DISIPLIN KERJA, PELATIHAN, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT PCI ELEKTRONIK INTERNASIONAL - Novisagita, Eka Rili; Wangdra, Yvonne (SCIENTIA JOURNAL, 2020)
This study was to determine the effect of work discipline, training, and communication on the performanceof employees of PT. PCI Electronics International. The population of this study was 500 employees, Thenumber of samples is calculated using Slovin formula. So, the sample in this study was 163. Dataanalysis methods used are descriptive analysis, data quality test, classic assumption test, regression, andhypothesis testing with the help of SPSS. The results of data analysis in this study shows that workdiscipline has a significant positive affect on employee performance with a t value of 5.939> t table1.65449, training has a significant positive affect on employee performance with a t value of 2.956> t table1.65449, communication significantly positive affect on employee performance with a value of t value3.979> t table 1.65449. Lastly, independent variables work discipline, training, and communicationsimultaneously affect employee performance with an F count of 42.479> F table 2.66. The results of thedeterminant coefficient analysis obtained 0.445 or 44.5%, which means the contribution of work disciplinevariables, training, and communication to employee performance by 44.5% the rest is influenced by othervariables outside of this study.